Landscape Profiling Analysis of DPP4 in Malignancies: Therapeutic Implication for Tumor Patients With Coronavirus Disease 2019 - Shu, Lingling; Liu, Yang; Li, Jinyuan; Wu, Xiaoping; Li, Yang; Huang, Hanying (Frontiers in Oncology, 2021)
Severe coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is characterized by pneumonia, lymphopenia, and cytokine storms. Patients with underlying conditions, and especially cancer patients with impaired immunity, are particularly vulnerable to SARS-CoV-2 infection and complications. Although angiotensin converting enzyme II (ACE2) has been identified as a cellular binding receptor for SARS-CoV-2, immunopathological changes in severe cancer patients support the investigation of additional potential receptors such as dipeptidyl peptidase 4 (DPP4), a key immunoregulator. However, a comprehensive profiling analysis of DPP4 in malignancies remains obscure. In this study, using different datasets, we demonstrated the expression of DPP4 in healthy tissues and pan-cancers, showing the risk of different cancer types towards SARS-CoV-2 infection according to DPP4 expression levels. DPP4 expression was positively correlated with infiltrating levels of various immune cells and showed strong correlations with diverse immune marker sets in pan-cancer patients analyzed by Tumor Immune Estimation Resource (TIMER). These findings suggest that increased DPP4 expression in specific cancer patients might account for the high susceptibility to SARS-CoV-2 infection and the induction of cytokine storms. Due to the critical role of DPP4 in immunometabolism, our results indicate that pharmacological inhibition of DPP4 might provide beneficial therapeutic effects for SARS-CoV-2 treatment together with other strategies in specific tumor patients.